ADAPTASI KEBIASAAN BARU DI MASA PANDEMI COVID-19: Studi Pendekatan Ushul Fiqih dan Psikologi - Nihayatur Rohmah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2021)
The Covid-19 pandemic has succeeded in changing the habits that we do every day at home, at school, at work, on the road, at the right place of worship and anywhere. New habits for healthier living must be continuously carried out in society and in every individual, so that they become social norms and new individual norms in everyday life. If the new habit is not carried out in a disciplined manner or is only carried out by a group of people, then this could be a threat that the corona virus outbreak will have a longer duration. Old habits that are often carried out, such as shaking hands, crowding / clustering, lazy to wash hands must begin to be abandoned because they support the transmission of Covid-19. Various responses and reactions are shown by the community, some are sad, anxious, afraid, anxious, worried, angry but there are also those who are calm or remain confident. Changing attitudes and behavior in society requires struggles in the form of adaptation or adjustment. Individuals in society always describe themselves with their changing environment, either autoplastically or alloplastically. Thus the relationship between Individuals who interact are always a relationship that influences each other (reciprocally). The adaptation of new habits in this pandemic period is not without purpose. Among them are as a community medium for survival and Conformity which is carried out openly so that it is visible to the public, with the aim of making individuals accepted in group or avoid Rejection from the group. The adaptation of this new habit in the pandemicovid-19 period is in accordance with the principle of benefit because in essence every commandment and prohibition of sharia "is basically for realizing the goals of sharia, which are returned to the rule of" attracting benefit and rejecting damage. Pandemi Covid-19 berhasil mengubah kebiasaan yang kita lakukan sehari-hari baik di rumah, di sekolah, di tempat kerja, di jalan, di tepat ibadah dan dimanapun. Kebiasaan baru untuk hidup lebih sehat harus terus menerus dilakukan di masyarakat dan setiap individu, sehingga menjadi norma sosial dan norma individu baru dalam kehidupan sehari hari. Bila kebiasaan baru tidak dilakukan secara disiplin atau hanya dilakukan oleh sekelompok orang saja, maka hal ini bisa menjadi ancaman wabah virus corona ini akan semakin panjang durasinya. Kebiasaan lama yang sering dilakukan, seperti berjabat tangan, berkerumun/ bergerombol, malas cuci tangan harus mulai ditinggalkan karena mendukung penularan Covid-19.Berbagai respon dan reaksi ditunjukkan oleh masyarakat, ada yang sedih, cemas, takut, gemas, khawatir, marah-marah, tetapi ada juga yang tenang atau tetap percaya diri.Perubahan sikap dan perilaku masyarakat ini membutuhkan perjuangan dalam bentuk adaptasi atau penyesuaian diri.Individu dalam masyarakat senantiasa menjelaskan dirinya dengan lingkungan hidupnya secara berubah-ubah, baik secara autoplastis atau alloplastis.Dengan demikian hubungan antara individu yang berinteraksi senantiasa merupakan hubungan yang saling mempengaruhi (timbal balik).Adaptasi kebiasaan baru di masa pandemic ini dilakukan bukan tanpa tujuan.Diantaranya adalah sebagai media masyarakat untuk bertahan hidup dan Konformitas yang dilakukan secara terbuka sehingga terlihat oleh umum, bertujuan agar individu diterima dalam kelompok atau menghindari penolakan dari kelompok.Adaptasi kebiasaan baru di masa pandemicovid-19 ini bersesuaian dengan asas kemaslahatan karenapada hakikatnya setiap perintah dan larangan syara’ pada dasarnya untuk mewujudkan tujuan syariah, yang dikembalikan pada satu kaidah “menarik kemaslahatan dan menolak kerusakan”.